Kinship Determination in Archeological Contexts Through DNA Analysis - Vai, Stefania; Amorim, Carlos Eduardo G.; Lari, Martina; Caramelli, David (Frontiers in Ecology and Evolution, 2020)
Knowing kinship relations between individuals in archaeological contexts is of great importance to understand social habits and structure in past human communities. Archaeological and anthropological analyses of burial sites and skeletal remains often allow us to infer connections between individuals, but only genetic analysis can provide a sound determination of kinship. Several case studies are now available in the literature that show the potentiality and limitations of different methodological approaches based on ancient DNA. Both experimental and computational strategies for kinship estimation on ancient samples are described in this review and we argue that, within a multidisciplinary approach, kinship inference contributes to the understanding of the biological and cultural patterns that characterized past societies.